2017
DOI: 10.1002/bdr2.1062
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis Is Responsible for Lipid Vacuolation in the Amniotic Epithelium of Fetal Gastroschisis

Abstract: The abnormal amniotic epithelial findings are supported by experimental evidence of the trafficking of host lipids into the chlamydiae inclusion. If not lethal, what harm will elementary bodies inflict to the developing embryo? Do these women have a greater pro-inflammatory response to an environmental exposure, whether cigarette smoking, change in partner, or a pathogen? Testing the hypothesis that Chlamydia trachomatis is responsible for amniotic epithelium vacuoles will be a critical first step. Birth Defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
(116 reference statements)
0
3
0
1
Order By: Relevance
“…Both UTIs and STIs occur more frequently among young sexually active women 10 11. In addition, young women appear comparatively more susceptible to STI, particularly Chlamydia trachomatis and gonorrhoea, due to cervical ectropion 12 13…”
Section: Introductionmentioning
confidence: 99%
“…Both UTIs and STIs occur more frequently among young sexually active women 10 11. In addition, young women appear comparatively more susceptible to STI, particularly Chlamydia trachomatis and gonorrhoea, due to cervical ectropion 12 13…”
Section: Introductionmentioning
confidence: 99%
“…However, the supplementation of water-soluble cholesterol did not lead to increased cell numbers under the conditions tested, indicating that this compound cannot be the only potential limiting growth factor. Apart from cholesterol, eukaryotic sphingomyelin was found in membranes of Chlamydia trachomatis ( Carabeo et al, 2003 ), and it was shown that Chlamydia need these host lipids for expansion and replication ( Feldkamp et al, 2017 ). Insects do not have sphingomyelin but instead contain ceramide phosphorylethanolamine ( Luukkonen et al, 1973 ).…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors may contribute to the higher risk among young mothers, and geographical and temporal variation in prevalence." Additionally, another infectious agent, chlamydia trachomatis, has been suggested by Feldkamp et al [51] as a risk factor for gastroschisis based on observation of the unusual finding of vacuolated amniotic epithelium with lipid droplets in gastroschisis placentas, combined with some experimental evidence of the trafficking of host lipids into the chlamydia intracellular inclusions.…”
Section: Maternal Illnesses Medication Use and Substance Abusementioning
confidence: 99%